2017
DOI: 10.1186/s12885-017-3879-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cells induced by inflammatory cytokines produce angiogenetic factors and promote prostate cancer growth

Abstract: BackgroundProstate is susceptible to infection and pro-inflammatory agents in a man’s whole life. Chronic inflammation might play important roles in the development and progression of prostate cancer. Mesenchymal stem cells (MSCs) are often recruited to the tumor microenvironment due to local inflammation. We have asked whether stimulation of MSCs by pro-inflammatory cytokines could promote prostate tumor growth. The current study investigated the possible involvement of MSCs stimulated by pro-inflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…The study showed that BM-MSCs resulted in prostate cancer progression through cell fusion. Similar results were shown by the Yang et al [7] study wherein tumor necrosis factor-α and interferon-γ treated MSCs were shown to promote prostate tumor growth in a syngeneic mouse model. The prostate tumor and tumor stroma secreted transforming growth factor-β1 have shown to induce transdifferentiation of the BM-MSCs into cancer-associated fibroblast aiding in the progression of cancer [8,9].…”
supporting
confidence: 85%
“…The study showed that BM-MSCs resulted in prostate cancer progression through cell fusion. Similar results were shown by the Yang et al [7] study wherein tumor necrosis factor-α and interferon-γ treated MSCs were shown to promote prostate tumor growth in a syngeneic mouse model. The prostate tumor and tumor stroma secreted transforming growth factor-β1 have shown to induce transdifferentiation of the BM-MSCs into cancer-associated fibroblast aiding in the progression of cancer [8,9].…”
supporting
confidence: 85%
“…IFN‐γ at concentrations from 5 ng/ml up to 100 ng/ml has been used to induce hMSC immune polarization with most of studies using IFN‐γ at concentrations between 20 ng/ml and 50 ng/ml . In addition to immune modulation, the influence of IFN‐γ on hMSC proliferation , trilineage differentiation , migration , transcriptome profile , and secretion of angiogenic and other tropic factors has been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Malhotra et al 45 found that PDGF-C was a direct transcriptional target of Nrf2. In addition, BMMSCs stimulated by pro-inflammatory cytokines increased the expression of PDGF via the Nrf2-HIF-1α pathway and promoted prostate cancer growth 46 . Based on Figure S5 , we suggest that Res promote the PDGF-DD expression of hucMSCs possibly through regulating Nrf2.…”
Section: Discussionmentioning
confidence: 99%